Integrin α6β1 Expressed in ESCs Instructs the Differentiation to Endothelial Cells. (June 2015) - Toya, Sophie P.; Wary, Kishore K.; Mittal, Manish; Li, Fei; Toth, Peter T.; Park, Changwon; Rehman, Jalees; Malik, Asrar B.
Abstract Adhesion of embryonic stem cells (ESCs) to the extracellular matrix may influence differentiation potential and cell fate decisions. Here, we investigated the inductive role of binding of integrin α6β1 expressed in mouse (m)ESCs to laminin‐1 (LN1) in mediating the differentiation of ESCs to endothelial cells (ECs). We observed that α6β1 binding to LN1 was required for differentiation to ECs. α6β1 functioned by recruiting the adaptor tetraspanin protein CD151, which activated FAK and Akt signaling and mediated the EC lineage‐specifying transcription factor Er71. In contrast, association of the ESC‐expressed α3β1, another highly expressed LN1 binding integrin, with CD151, prevented α6β1‐mediated differentiation. CD151 thus functioned as a bifurcation router to direct ESCs toward ECs when α6β1 associated with CD151, or prevented transition to ECs when α3β1 associated with CD151. These observations were recapitulated in mice in which α6 integrin or CD151 knockdown reduced the expression of Er71‐regulated angiogenesis genes and development of blood vessels. Thus, interaction of α6β1 in ESCs with LN1 activates α6β1/CD151 signaling which programs ESCs toward the EC lineage fate. Stem Cells2015;33:1719–1729